A photothermal working fluid, its preparation method and application
Patent Information
- Application Number
- CN202611185526.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-06
- Publication Date
- 2026-10-20
AI Technical Summary
然而,MXene纳米片在水相中容易发生片层堆叠、聚集、沉降和氧化,导致工作流体在储存和循环过程中出现稳定性下降及光热性能衰减
[0058](1)本发明利用界面交联聚合物胶体囊作为MXene纳米片的稳定载体,可有效抑制MXene纳米片层堆叠、聚集和沉降,提高工作流体的长期分散稳定性;
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of solar photothermal conversion materials and nanofluid technology, specifically relating to a photothermal working fluid, its preparation method and application, and particularly an MXene / polymer colloidal capsule photothermal working fluid, its preparation method and application. Background Technology
[0002] Direct absorption solar collectors directly absorb solar radiation and convert it into heat energy through a working fluid, reducing heat transfer losses between the absorber plate and the fluid in traditional surface absorption collectors. The performance of this type of system is highly dependent on the working fluid's solar absorption capacity, photothermal conversion efficiency, thermal conductivity, specific heat capacity, viscosity, and long-term cycling stability. Traditional working fluids such as water, oil, or aqueous glycol solutions typically suffer from weak solar absorption capacity and limited thermal conductivity, making them unsuitable for efficient solar thermal utilization.
[0003] MXene materials, especially Ti3C2T x MXene materials, possessing broad-spectrum absorption, high thermal conductivity, and excellent photothermal conversion capabilities, are candidate materials for constructing solar photothermal nanofluids. However, MXene nanosheets are prone to stacking, aggregation, sedimentation, and oxidation in aqueous solutions, leading to decreased stability and reduced photothermal performance of the working fluid during storage and cycling. Existing technologies often employ surface modification, the addition of surfactants, or polymer dispersants to improve MXene stability, but these methods often struggle to simultaneously achieve long-term dispersion stability, low viscosity, high specific heat capacity, and efficient photothermal conversion performance.
[0004] Therefore, there is an urgent need to develop a solar thermal working fluid that can achieve efficient photothermal conversion with low MXene addition levels, while also possessing good dispersion stability, cycle stability, and fluidity. Summary of the Invention
[0005] In view of the shortcomings of the prior art, the purpose of this invention is to provide a photothermal working fluid, its preparation method and application.
[0006] To achieve this objective, the present invention adopts the following technical solution:
[0007] In a first aspect, the present invention provides a photothermal working fluid comprising a continuous aqueous phase and a polymer colloidal capsule dispersed in the continuous aqueous phase, the polymer colloidal capsule comprising an oil phase droplet and a polymer colloidal capsule shell layer located outside the oil phase droplet, the polymer colloidal capsule shell layer being loaded with MXene nanosheets.
[0008] This invention addresses the problems of easy aggregation, sedimentation, and photothermal performance degradation of MXene nanosheets in traditional water-based nanofluids by anchoring MXene nanosheets to the surface of interfacially cross-linked polymer colloidal capsules. This results in a working fluid with good dispersion stability, photothermal conversion efficiency, and cycle stability, which can be used in direct absorption solar collectors, photovoltaic / photothermal systems, and solar thermal management.
[0009] In some embodiments, the concentration of the MXene nanosheets in the photothermal working fluid is 1-500 ppm, such as 1 ppm, 2 ppm, 5 ppm, 10 ppm, 15 ppm, 18 ppm, 20 ppm, 22 ppm, 25 ppm, 28 ppm, 30 ppm, 32 ppm, 35 ppm, 38 ppm, 40 ppm, 45 ppm, 50 ppm, 55 ppm, 60 ppm, 100 ppm, 200 ppm, 300 ppm, 400 ppm, 500 ppm, etc., preferably 15-60 ppm.
[0010] In some embodiments, the MXene nanosheets are Ti3C2T x Nanosheets, T x The terminal functional group is selected from any one or a combination of at least two of -O, -OH or -F, preferably including a combination of -O, -OH and -F. In current conventional MXene nanosheet preparation methods, the above functional groups coexist in a mixed form on the material surface.
[0011] In this invention, since the surface of MXene nanosheets is typically negatively charged, while the surface of the polymer colloidal shell layer contains positively charged quaternary ammonium salt groups, MXene nanosheets can be anchored to the surface of the colloidal shell layer through electrostatic adsorption. Simultaneously, the end groups on the MXene surface can also undergo hydrogen bonding, coordination, or covalent interactions with the hydroxyl, epoxy, or amine groups in the colloidal shell layer, thereby further enhancing the interfacial bonding stability. Therefore, in this invention, the MXene nanosheets are anchored to the colloidal capsule interface through any one or a combination of at least two of electrostatic, hydrogen bonding, covalent, or coordination interactions, resulting in an MXene / polymer colloidal capsule photothermal working fluid.
[0012] In some embodiments, the polymer colloidal shell layer is formed by the self-assembly of functionalized polymer latex particles at the oil-water interface and subsequent interfacial crosslinking.
[0013] In some embodiments, the functionalized polymer latex particles comprise a polystyrene core and an amphiphilic functional polymer layer located on the surface of the polystyrene core.
[0014] In some embodiments, the amphiphilic functional polymer layer preferably comprises a copolymer formed from 2-diethylaminoethyl acrylate and glycidyl methacrylate.
[0015] Secondly, the present invention provides a photothermal working fluid comprising an aqueous phase, an oil phase, and an MXene nanosheet dispersion. The aqueous phase contains functionalized polymer latex particles, and the oil phase contains a crosslinking agent. The functionalized polymer latex particles undergo self-assembly and interfacial crosslinking at the oil-water interface to obtain a polymer colloidal shell layer. The polymer colloidal shell layer coats the outside of the droplets formed in the oil phase, and the MXene nanosheets are loaded on the polymer colloidal shell layer.
[0016] In some embodiments, the concentration of the MXene nanosheets in the photothermal working fluid is 1-500 ppm, such as 1 ppm, 2 ppm, 5 ppm, 10 ppm, 15 ppm, 18 ppm, 20 ppm, 22 ppm, 25 ppm, 28 ppm, 30 ppm, 32 ppm, 35 ppm, 38 ppm, 40 ppm, 45 ppm, 50 ppm, 55 ppm, 60 ppm, 100 ppm, 200 ppm, 300 ppm, 400 ppm, 500 ppm, etc., preferably 15-60 ppm.
[0017] In some embodiments, the concentration of the MXene nanosheet aqueous dispersion is 1-10 mg / mL, such as 1 mg / mL, 2 mg / mL, 3 mg / mL, 4 mg / mL, 5 mg / mL, 6 mg / mL, 8 mg / mL, 9 mg / mL, 10 mg / mL, etc., preferably 5 mg / mL.
[0018] In some embodiments, the concentration of the functionalized polymer latex particles in the aqueous phase is 0.1-10 wt%, for example, 0.1 wt%, 0.5 wt%, 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, 10 wt%, etc.
[0019] In some embodiments, the surface of the functionalized polymer latex particles contains any one or a combination of at least two of amine groups, quaternary ammonium groups, epoxy groups, or hydroxyl groups.
[0020] In some embodiments, the functionalized polymer latex particles comprise a polystyrene core and an amphiphilic functional polymer layer located outside the polystyrene core.
[0021] In some embodiments, the amphiphilic functional polymer comprises a copolymer of 2-diethylaminoethyl acrylate and glycidyl methacrylate.
[0022] In some embodiments, the molar ratio of 2-diethylaminoethyl acrylate to glycidyl methacrylate is 1:(0.2-0.9), such as 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, etc., preferably 24:13.
[0023] This invention can regulate the surface charge, wettability, and reactivity of latex particles by adjusting the ratio of the two monomers, thereby improving their adsorption stability at the oil-water interface and their subsequent interfacial crosslinking ability.
[0024] In some embodiments, the mass ratio of styrene monomer to amphiphilic functional polymer is (4-6):1, for example 4:1, 4.2:1, 4.5:1, 4.8:1, 5:1, 5.2:1, 5.5:1, 5.8:1, 6:1, etc., preferably 4.95:1.
[0025] In some embodiments, the crosslinking agent includes an epoxy crosslinking agent, preferably polypropylene glycol diglycidyl ether.
[0026] In some embodiments, the concentration of the crosslinking agent in the oil phase is 1-10 mg / mL, such as 1 mg / mL, 2 mg / mL, 3 mg / mL, 4 mg / mL, 5 mg / mL, 6 mg / mL, 8 mg / mL, 9 mg / mL, 10 mg / mL, etc., preferably 4 mg / mL.
[0027] In some embodiments, the volume ratio of the aqueous phase to the oil phase is (0.1-10):1, such as 0.1:1, 0.5:1, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, etc.
[0028] Preferably, the mass ratio of the oil phase to the functionalized polymer latex particles is (50-100):1, for example, 50:1, 55:1, 60:1, 65:1, 70:1, 72:1, 75:1, 78:1, 80:1, 90:1, 100:1, etc., and preferably (70-80):1.
[0029] In some embodiments, the oil phase comprises any one or a combination of at least two of n-dodecane, C8-C20 alkanes, ester oils, or silicone oils.
[0030] Thirdly, the present invention provides a method for preparing a photothermal working fluid as described in the first or second aspect, the method comprising:
[0031] S1. An aqueous phase containing functionalized polymer latex particles is mixed with an oil phase containing a crosslinking agent to form a Pickering emulsion;
[0032] S2. At the oil-water interface of the Pickering emulsion, functionalized polymer latex particles undergo self-assembly and interfacial cross-linking at the oil-water interface to obtain a polymer colloidal shell layer, which coats the outside of the droplets formed by the oil phase.
[0033] S3. The dispersion obtained in step S2 is mixed with MXene nanosheets, so that the MXene nanosheets are loaded onto the polymer colloidal shell layer to obtain the photothermal working fluid.
[0034] In some embodiments, the preparation method includes:
[0035] (1) Preparation of amphiphilic functional polymers containing amine and epoxy groups;
[0036] (2) Using an amphiphilic functional polymer as a stabilizer, styrene monomer and 4-vinylbenzyl chloride were subjected to surfactant-free emulsion polymerization to obtain functionalized polymer latex particles. 4-vinylbenzyl chloride was introduced to partially quaternize the amine groups, so that the surface of the obtained functionalized polymer latex particles was positively charged.
[0037] (3) Functionalized polymer latex particles are dispersed in the aqueous phase and mixed with the oil phase containing crosslinking agent to form Pickering emulsion. During the emulsification process, at the oil-water interface of the Pickering emulsion, the functionalized polymer latex particles undergo self-assembly and crosslinking reaction at the oil-water interface to obtain a polymer colloidal shell layer, which covers the outside of the droplets formed in the oil phase.
[0038] (4) The dispersion obtained in step (3) is mixed with the aqueous dispersion of MXene nanosheets to load the MXene nanosheets onto the polymer colloidal shell layer, thereby obtaining the photothermal working fluid.
[0039] In some embodiments, the amphiphilic functional polymer is prepared by reversible addition-fragmentation chain transfer polymerization, wherein the monomers include 2-diethylaminoethyl acrylate and glycidyl methacrylate.
[0040] In some embodiments, step (1) specifically includes:
[0041] 2-Diethylaminoethyl acrylate, glycidyl methacrylate, chain transfer agent and initiator are dissolved in an organic solvent and subjected to a reversible addition-fragmentation chain transfer polymerization reaction under an inert atmosphere to obtain the amphiphilic functional polymer. Preferably, the polymerization reaction is carried out at a temperature of 50-90°C for 4-24 h.
[0042] Preferably, the molar ratio of 2-diethylaminoethyl acrylate to glycidyl methacrylate is 1:(0.2-0.9), for example 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, etc., and more preferably 24:13.
[0043] In some embodiments, step (2) specifically includes:
[0044] The amphiphilic functional polymer is dispersed or dissolved in water, styrene monomer and 4-vinylbenzyl chloride are added, and a water-soluble initiator is added under an inert atmosphere to carry out surfactant-free emulsion polymerization to obtain the functionalized polymer latex particles.
[0045] Preferably, the mass ratio of the styrene monomer to 4-vinylbenzyl chloride is 1:(0.0001-0.001), for example 1:0.0001, 1:0.0005, 1:0.0006, 1:0.0008, 1:0.001, etc., and preferably 1:0.00032.
[0046] Preferably, the mass ratio of the amphiphilic functional polymer to the total mass of styrene and 4-vinylbenzyl chloride is 1:(4-6), more preferably 1:4.95.
[0047] Preferably, the temperature for surfactant-free emulsion polymerization is 50-70℃, such as 50℃, 55℃, 58℃, 60℃, 65℃, 70℃, etc., preferably 60℃, and the time is 12-30 h, such as 12 h, 15 h, 18 h, 20 h, 24 h, etc., for example 24 h.
[0048] The functionalized polymer latex particles have a positive charge on their surface, enabling them to be stably dispersed in an aqueous phase and used as a Pickering emulsifier at the oil-water interface.
[0049] In some embodiments, step (3) specifically includes:
[0050] Functionalized polymer latex particles are dispersed in an aqueous phase at a concentration of 0.1-10 wt%, and a crosslinking agent is pre-dissolved in an oil phase at a concentration of 1-10 mg / mL. The aqueous and oil phases are mixed at a volume ratio of (0.1-10):1, and then shear emulsified to form an oil-in-water Pickering emulsion. Preferably, 5 mL of a 1 wt% aqueous dispersion of functionalized polymer latex particles is emulsified with 5 mL of n-dodecane containing 4 mg / mL crosslinking agent.
[0051] The process is carried out during emulsification. During emulsification, the crosslinking agent reacts with the hydroxyl, amine, or epoxy groups on the surface of the functionalized polymer latex particles at the oil-water interface, causing the functionalized polymer latex particles at the oil-water interface to crosslink with each other and form a polymer colloidal shell layer with mechanical stability. After static aging, a dispersion is obtained.
[0052] Preferably, the crosslinking agent comes into contact with the functionalized polymer latex particles during emulsification at room temperature and begins to undergo interfacial crosslinking.
[0053] Preferably, the shear emulsification time is 1-5 min, such as 1 min, 2 min, 3 min, 4 min, 5 min, etc.; after emulsification, it is left to stand at room temperature for 6-24 h, such as 6 h, 8 h, 10 h, 12 h, 14 h, 15 h, 16 h, 18 h, 20 h, 24 h, etc. More preferably, shear emulsification is performed at 12000 rpm for 2 min, followed by standing at room temperature for 12 h.
[0054] In some embodiments, step (4) specifically includes:
[0055] Add an aqueous dispersion of MXene nanosheets to the dispersion obtained in step (3) and stir to mix. Under stirring conditions, the MXene nanosheets come into contact with the surface of the positively charged polymer colloidal shell layer and are loaded onto the surface of the colloidal shell layer through electrostatic interaction, hydrogen bonding, coordination or covalent interaction to obtain the MXene / polymer colloidal capsule photothermal working fluid.
[0056] Fourthly, the present invention provides the application of the photothermal working fluid as described in the first or second aspect in a solar photothermal conversion system, a direct absorption solar collector, a photovoltaic / photothermal system, or a solar thermal management system.
[0057] Compared with the prior art, the present invention has the following beneficial effects:
[0058] (1) The present invention utilizes interfacial cross-linked polymer colloidal capsules as a stable carrier for MXene nanosheets, which can effectively inhibit the stacking, aggregation and sedimentation of MXene nanosheets and improve the long-term dispersion stability of the working fluid.
[0059] (2) In this invention, MXene nanosheets are confined at the oil-water interface of the colloidal capsule, so that the colloidal capsule interface serves as both a stable structure and a photothermal coupling region, which is beneficial to enhancing the absorption of sunlight and the efficiency of local heat conversion.
[0060] (3) The present invention can achieve high photothermal conversion performance at a low MXene nanosheet concentration, while maintaining high specific heat capacity, moderate thermal conductivity improvement and low flow resistance, making it suitable for use in a circulating solar thermal utilization system.
[0061] (4) The preparation method provided by the present invention has mild conditions and adjustable components, and is suitable for direct absorption solar collectors, photovoltaic / photothermal systems and solar thermal management devices. Attached Figure Description
[0062] Figure 1 The nuclear magnetic resonance spectrum of the amphiphilic functional polymer prepared in Example 1;
[0063] Figure 2 The infrared spectrum of the amphiphilic functional polymer prepared in Example 1;
[0064] Figure 3 Scanning electron microscope image of the functional polymer latex particles prepared in Example 2;
[0065] Figure 4 The scanning electron microscope image and elemental distribution map of the polymer colloidal capsules prepared in Example 3 are shown below.
[0066] Figure 5 The images show scanning electron microscope (SEM) images and elemental distribution maps of the Mxene nanosheets loaded on the surface of polymer capsules (MXene / polymer capsules) in Examples 4-4.
[0067] Figure 6 A comparison graph showing the energy absorption of MXene / water (Comparative Example 1), MXene / latex particle dispersion (Comparative Example 3), and MXene / polymer colloidal capsule working fluid (Example 4) at different MXene concentrations;
[0068] Figure 7 The graph shows the change in average droplet diameter over storage time for uncrosslinked colloidal capsules (Comparative Example 2), crosslinked colloidal capsules (Example 3), and MXene / crosslinked colloidal capsules (Examples 4-4).
[0069] Figure 8 Temperature response graph of MXene / polymer colloidal capsule working fluid (Examples 4-4) after 100 light-cooling cycles. Detailed Implementation
[0070] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention in any way.
[0071] Unless otherwise specified, the raw materials involved in the following specific embodiments of the present invention are all conventional materials in the art, and can be purchased from commercially available products. Some of the raw materials are sourced as follows:
[0072] MXene nanosheets: monolayer Ti3C2T x MXene aqueous dispersion, with a concentration of 5 mg / mL and a purity of 99.9%, was purchased from Xinxi Technology (China).
[0073] Example 1
[0074] This embodiment provides a method for preparing an amphiphilic functional polymer, as follows:
[0075] In a 50 mL round-bottom flask, 1000 mg (5.78 mmol) of 2-diethylaminoethyl acrylate, 485.92 mg (3.13 mmol) of glycidyl methacrylate, and 4.6 mL of N,N-dimethylformamide were added. Then, 27.48 mg (0.12 mmol) of 2-cyano-2-propyl dithiobenzoate as a chain transfer agent, 4 mg (0.02 mmol) of azobisisobutyronitrile as an initiator, and 842.31 mg (7.23 mmol) of trifluoroacetic acid were added. After degassing with argon for 30 min, the reaction was carried out in an oil bath at 70 °C for 8 h. After the reaction was completed, the mixture was exposed to air and immediately placed in an ice bath at 0 °C to terminate the reaction. 1,8-bis(dimethylamino)naphthalene was added at 1.2 times the initial amount of trifluoroacetic acid, and the mixture was stirred vigorously for 30 min. The crude product was dialyzed against anhydrous ethanol at room temperature for 48 h, with the ethanol being replaced every 12 h; subsequently, it was concentrated under reduced pressure, redispersed in deionized water, and freeze-dried to obtain p(DEAEA). 42 -stat-GlyMA 26 Amphiphilic functional polymers.
[0076] like Figure 1As shown, in the 1H NMR spectrum of the amphiphilic functional polymer, the vinyl proton signal of the monomer disappears at δ 5.5-6.5 ppm, while the characteristic signal of the methylene proton adjacent to the tertiary amine in the DEAEA repeating unit at δ 2.6-2.8 ppm and the characteristic signals of the epoxy methine and methylene protons in the GlyMA repeating unit at δ 3.2-3.8 ppm appear, indicating that both DEAEA and GlyMA have participated in polymerization. Based on the integral ratio of the corresponding characteristic peaks to the aromatic proton peaks of the CPDB terminal group, the degrees of polymerization of DEAEA and GlyMA in the obtained polymer are calculated to be approximately 42 and 26, respectively, which is close to the target composition p(DEAEA). 42 -stat-GlyMA 26 Consistent.
[0077] like Figure 2 As shown, the obtained polymer is at approximately 1450 cm⁻¹ -1 and 1380 cm -1 An absorption peak for the methylene bending vibration appears at approximately 1730 cm⁻¹. -1 An absorption peak for the C=O stretching vibration of the ester group appears at approximately 1180 cm⁻¹. -1 and 1160 cm -1 Absorption peaks for COC and CN stretching vibrations appeared at approximately 3365 cm⁻¹; additionally, absorption peaks were observed at approximately 3365 cm⁻¹. -1 The broad absorption peak at the specified location is attributed to the stretching vibration of hydroxyl groups, indicating that some epoxy groups underwent hydrolysis during aqueous treatment. The above-mentioned 1H NMR and IR spectroscopy results jointly demonstrate that DEAEA and GlyMA were successfully copolymerized, and the resulting amphiphilic functional polymer simultaneously contains functional groups such as tertiary amines, epoxy groups, ester groups, and hydroxyl groups.
[0078] Example 2
[0079] This embodiment provides a method for preparing functionalized polymer latex particles, as follows:
[0080] p(DEAEA) prepared in Example 1 42 -stat-GlyMA 261000 mg of the amphiphilic functional polymer was added to a 100 mL round-bottom flask and dissolved in 12.0 mL of deionized water with stirring at 250 rpm. 5.44 mL (47.6 mmol) of styrene and 1.6 mg (10.5 μmol) of 4-vinylbenzyl chloride were added sequentially. The mixture was degassed by argon bubbling for 30 min and heated to 60 °C. An initiator aqueous solution prepared from 56 mg (0.34 mmol) of azobisisobutyramidine hydrochloride and 2.5 mL of deionized water was then added dropwise. The reaction was carried out at 60 °C for 24 h with continuous stirring. After the reaction, the latex particles were purified by three centrifugation-redispersion cycles with deionized water, each centrifuged for 5 min at 3000 rpm at 25 °C. The purified latex particles were dried at 40 °C for 24 h to obtain the functionalized polymer latex particles.
[0081] like Figure 3 Scanning electron microscopy (SEM) images show that the obtained functionalized polymer latex particles are uniformly spherical with a hydrated particle size of 238.7 nm, a polydispersity index of 0.137, and a Zeta potential of +21.28 mV; the water contact angle of the latex particle film is approximately 77.98°. These results indicate that the amphiphilic functionalized polymer is enriched on the surface of polystyrene particles, imparting them with a positive charge and wettability suitable for adsorption at the oil-water interface.
[0082] Example 3
[0083] This embodiment provides a method for preparing a polymer colloidal capsule dispersion.
[0084] The functionalized polymer latex particles obtained in Example 2 were formulated into a 1 wt% aqueous dispersion, and 5 mL of the dispersion was taken. The crosslinking agent, polypropylene glycol diglycidyl ether, was pre-dissolved in n-dodecane at a concentration of 4 mg / mL, and 5 mL of the resulting oil phase was taken. The aqueous and oil phases were mixed and homogenized at 12000 rpm for 2 min using a D160 / 10 homogenizer to obtain an oil-in-water Pickering emulsion. During emulsification, the crosslinking agent in the oil phase contacted and interfacially crosslinked with the functionalized polymer latex particles located at the oil-water interface. The resulting emulsion was allowed to stand at room temperature for 12 h to further solidify the shell layer, yielding a polymer colloidal capsule dispersion.
[0085] like Figure 4 As shown, the colloidal capsule is micron-sized spherical, with amphiphilic functional polymers enriched on the surface. The nitrogen elements distributed on the surface come from the tertiary amine groups in the DEAEA polymer structure and the quaternary ammonium salt groups on the surface of the polymer latex particles.
[0086] like Figure 7As shown, compared to the uncrosslinked colloidal capsules of Comparative Example 2 (where the average droplet diameter increased significantly with storage time, reaching approximately 220 μm by day 56), the present invention obtained crosslinked colloidal capsules by introducing a crosslinking agent. The average droplet diameter of the crosslinked colloidal capsules remained within approximately 70 μm during the same period, indicating that adding a crosslinking agent and performing interfacial crosslinking during emulsification can significantly inhibit droplet co-aggregation and ripening.
[0087] Example 4
[0088] This embodiment provides a method for preparing a photothermal working fluid, as follows:
[0089] A monolayer of Ti3C2T with a concentration of 5 mg / mL was used. x The MXene aqueous dispersion was sonicated for 30 seconds using an ultrasonic cell disruptor at 45% power. Under room temperature and slow magnetic stirring, the MXene aqueous dispersion was dropwise added to the polymer colloidal capsule dispersion prepared in Example 3. The amount added was calculated based on the final working fluid volume, resulting in final MXene concentrations of 15 ppm, 30 ppm, 45 ppm, and 60 ppm, respectively. After the addition was complete, the mixture was slowly stirred until homogeneous and allowed to stand to equilibrate, allowing the negatively charged MXene nanosheets to adsorb and anchor onto the positively charged polymer colloidal capsule surface, yielding the photothermal working fluids of Examples 4-1, 4-2, 4-3, and 4-4, respectively.
[0090] like Figure 5 As shown in Examples 4-4, adsorption monolayer Ti3C2T x MXene colloidal capsules are micron-sized spherical, with amphiphilic functional polymers enriched on the surface to provide the functional groups required for adsorption. Nitrogen elements are distributed, and titanium elements are distributed on the surface of the capsules due to MXene adsorption. The resulting photothermal working fluid has a uniform appearance, with no visible agglomeration or sedimentation. Taking 60 ppm MXene as an example... Figure 6 As shown, the MXene / polymer colloidal capsule working fluid absorbed 1702 J of energy under simulated sunlight irradiation for 1200 s, which is approximately 10.7% higher than the 1537 J of the MXene / aqueous dispersion with the same MXene concentration, achieving a solar-to-thermal energy conversion efficiency of 77.9%. Figure 8 As shown, the working fluid maintains a stable temperature response after 100 consecutive light-cooling cycles.
[0091] Example 5
[0092] This embodiment provides a method for preparing polymer colloidal capsule dispersions with different concentration ratios, as follows:
[0093] The functionalized polymer latex particles obtained in Example 2 were formulated into a 5 wt% aqueous dispersion, and 5 mL of this dispersion was taken. The crosslinking agent, polypropylene glycol diglycidyl ether, was pre-dissolved in n-dodecane at a concentration of 10 mg / mL, and 5 mL of the resulting oil phase was taken. The aqueous and oil phases were mixed and homogenized at 12000 rpm for 2 min using a D160 / 10 homogenizer to obtain an oil-in-water Pickering emulsion. During emulsification, the crosslinking agent in the oil phase contacted and interfacially crosslinked with the functionalized polymer latex particles located at the oil-water interface. The resulting emulsion was allowed to stand at room temperature for 12 h to further solidify the shell layer, yielding a polymer colloidal capsule dispersion.
[0094] The above results indicate that by changing the concentration and ratio of each component in Pickering emulsification, polymer colloidal capsule dispersions with different particle sizes can be obtained.
[0095] Example 6
[0096] This embodiment investigates the effect of the volume ratio of the aqueous phase to the oil phase on the formation of Pickering emulsions.
[0097] p(DEAEA) prepared using Example 2 42 -stat-GlyMA 26 Polystyrene functionalized polymer latex particles were prepared into a 1 wt% aqueous dispersion; samples were prepared with n-dodecane as the oil phase at water-to-oil volume ratios of 3:1, 3:2, 1:1, and 2:3, and emulsified under the same homogenization conditions as in Example 3.
[0098] In this embodiment, polymer colloidal capsules and MXene / polymer colloidal capsule photothermal working fluids were obtained. To achieve better application results, the present invention selected polymer colloidal capsules and MXene / polymer colloidal capsule photothermal working fluids obtained under the homogeneous conditions described in Example 3 with a latex particle concentration of 1 wt% for verification. The performance and application effects of the MXene / polymer colloidal capsule photothermal working fluids obtained in other embodiments are similar, all exhibiting good dispersion stability, photothermal conversion efficiency, and cycle stability.
[0099] Comparative Example 1
[0100] This comparative example provides a photothermal working fluid.
[0101] The photothermal working fluid provided in this comparative example is an aqueous dispersion of MXene nanosheets with concentrations of 15 ppm (Comparative Example 1-1), 30 ppm (Comparative Example 1-2), and 45 ppm (Comparative Example 1-3).
[0102] The aqueous dispersion provided in this comparative example is prone to lamellae aggregation and sedimentation during the standing process. Deposition can be observed after about 3 days, and the supernatant gradually becomes lighter after about 7 days, indicating that the content of effectively dispersed MXene continues to decrease. In contrast, the MXene / polymer colloidal capsule photothermal working fluid obtained in Example 4 can maintain a uniform appearance during the observation period at the same MXene concentration, without obvious sedimentation or oil-water separation.
[0103] Meanwhile, under the conditions of MXene concentration of 60 ppm and irradiation for 1200 s, the MXene / aqueous dispersion absorbed approximately 1537 J of energy, while the MXene / polymer colloidal capsule photothermal working fluid absorbed approximately 1702 J of energy, which is about 10.7% higher than that of the MXene / aqueous dispersion, and can achieve a solar-to-thermal energy conversion efficiency of about 77.9%. This result shows that confining and anchoring MXene at the polymer colloidal capsule interface can simultaneously improve the dispersion stability of MXene and the photothermal utilization efficiency.
[0104] Comparative Example 2
[0105] This comparative example provides a photothermal working fluid.
[0106] The difference from Example 3 is that no crosslinking agent is introduced in this comparative example; that is, the working fluid is an uncrosslinked colloidal capsule working fluid.
[0107] Comparative Example 3
[0108] This comparative example provides a photothermal working fluid.
[0109] The photothermal working fluid provided in this comparative example is an aqueous dispersion containing both MXene nanosheets and functionalized polymer latex particles.
[0110] Functionalized latex particles have positive charges and reactive surface groups, which can cause certain electrostatic adsorption with negatively charged MXene nanosheets; however, due to the lack of an oil-water interface, cross-linked shell, and spatial confinement structure of colloidal capsules in this system, MXene nanosheets are mainly located in the aqueous phase or near the outer surface of latex particles, making it difficult to form a stable interfacial photothermal coupling domain.
[0111] The dynamic photothermal results show that although the MXene / latex particle dispersion system exhibits enhanced heating with increasing MXene concentration, its overall response is lower than that of the MXene / polymer colloidal capsule photothermal working fluid. This indicates that latex particles themselves are not the main source of photothermal contribution, and simple latex particle adsorption cannot replace the cross-linked colloidal capsule interface structure.
[0112] Comparative Example 4
[0113] This comparative example provides a photothermal working fluid.
[0114] The photothermal working fluid provided in this comparative example is the polymer colloidal capsule dispersion obtained in Example 3.
[0115] Compared to uncrosslinked Pickering emulsions, interfacial crosslinked polymer capsules exhibit better structural stability, suppressing oil droplet co-agglomeration and Ostwald ripening, and maintaining a narrower droplet size distribution during long-term standing.
[0116] The dynamic photothermal results show that, without the addition of MXene, water, latex particle dispersion, and polymer colloidal capsule dispersion can all generate a certain temperature rise under light irradiation. However, the solar-to-thermal energy conversion efficiency of the polymer colloidal capsule system without MXene loading is lower than that of the MXene / polymer colloidal capsule photothermal working fluid.
[0117] These results indicate that the polymer colloidal capsules mainly provide a stable interfacial carrier and fluid structure basis, while the efficient photothermal conversion mainly comes from the synergistic effect between the MXene nanosheets and the colloidal capsule interface.
[0118] Overall comparison results: Comparing Comparative Examples 1-4 with Example 4, it can be seen that the MXene / aqueous dispersion has good initial light absorption capacity, but its long-term stability is insufficient, and it is prone to sedimentation and performance degradation; the latex particle dispersion system can provide certain surface adsorption sites, but it lacks cross-linked oil-water interfaces, making it difficult to fully utilize the interface confinement and photothermal coupling effects; the polymer colloidal capsule system without MXene loading has good structural stability, but its photothermal conversion capacity is limited.
[0119] The MXene / polymer colloidal capsule photothermal working fluid obtained in this embodiment of the invention possesses both the stable interface structure of cross-linked colloidal capsules and the broad-spectrum absorption capability of MXene nanosheets. It can achieve an absorption energy of about 1702 J and a photothermal conversion efficiency of about 77.9% at a low addition amount of 60 ppm MXene, and maintain a stable response under cyclic light-cooling conditions.
[0120] Therefore, this invention does not simply add MXene to an aqueous phase or a latex particle dispersion, but rather constructs an interface-programmable polymer colloidal shell layer to effectively anchor MXene nanosheets at the oil-water interface, thereby achieving a comprehensive improvement in dispersion stability, photothermal properties, and flow applicability.
[0121] The present invention has been illustrated through the above embodiments, but the present invention is not limited to the above process steps, that is, it does not mean that the present invention must rely on the above process steps to be implemented. Those skilled in the art should understand that any improvements to the present invention, equivalent substitutions of the raw materials used in the present invention, additions of auxiliary components, and selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A photothermal working fluid, characterized in that, The photothermal working fluid includes a continuous aqueous phase and a polymer colloidal capsule dispersed in the continuous aqueous phase. The polymer colloidal capsule includes an oil phase droplet and a polymer colloidal capsule shell layer located outside the oil phase droplet. MXene nanosheets are loaded on the polymer colloidal capsule shell layer.
2. The photothermal working fluid according to claim 1, characterized in that, In the photothermal working fluid, the concentration of the MXene nanosheets is 1-500 ppm, preferably 15-60 ppm; And / or, the MXene nanosheets are Ti3C2T x Nanosheets, T x It is a terminal functional group, selected from any one or a combination of at least two of -O, -OH or -F.
3. A photothermal working fluid, characterized in that, The photothermal working fluid includes an aqueous phase, an oil phase, and an MXene nanosheet dispersion. The aqueous phase contains functionalized polymer latex particles, and the oil phase contains a crosslinking agent. The functionalized polymer latex particles undergo self-assembly and interfacial crosslinking at the oil-water interface to obtain a polymer colloidal shell layer. The polymer colloidal shell layer covers the outside of the droplets formed in the oil phase, and the MXene nanosheets are loaded on the polymer colloidal shell layer.
4. The photothermal working fluid according to claim 3, characterized in that, In the photothermal working fluid, the concentration of the MXene nanosheets is 1-500 ppm, preferably 15-60 ppm; And / or, the concentration of the MXene nanosheet aqueous dispersion is 1-10 mg / mL.
5. The photothermal working fluid according to claim 3 or 4, characterized in that, In the aqueous phase, the concentration of the functionalized polymer latex particles is 0.1-10 wt%; Preferably, the surface of the functionalized polymer latex particles contains any one or a combination of at least two of the following: amine groups, quaternary ammonium salt groups, epoxy groups, or hydroxyl groups; Preferably, the functionalized polymer latex particles comprise a polystyrene core and an amphiphilic functional polymer layer located outside the polystyrene core; Preferably, the amphiphilic functional polymer comprises a copolymer of 2-diethylaminoethyl acrylate and glycidyl methacrylate.
6. The photothermal working fluid according to any one of claims 3-5, characterized in that, The crosslinking agent includes an epoxy crosslinking agent, preferably polypropylene glycol diglycidyl ether; Preferably, in the oil phase, the concentration of the crosslinking agent is 1-10 mg / mL; Preferably, the volume ratio of the aqueous phase to the oil phase is (0.1-10):1; Preferably, the mass ratio of the oil phase to the functionalized polymer latex particles is (50-100):1, more preferably (70-80):1; Preferably, the oil phase comprises any one or a combination of at least two of the following: n-dodecane, C8-C20 alkanes, ester oils, or silicone oils.
7. A method for preparing a photothermal working fluid as described in any one of claims 1-6, characterized in that, The preparation method includes: S1. An aqueous phase containing functionalized polymer latex particles is mixed with an oil phase containing a crosslinking agent to form a Pickering emulsion; S2. At the oil-water interface of the Pickering emulsion, functionalized polymer latex particles undergo self-assembly and interfacial cross-linking at the oil-water interface to obtain a polymer colloidal shell layer, which coats the outside of the droplets formed by the oil phase. S3. The dispersion obtained in step S2 is mixed with MXene nanosheets, so that the MXene nanosheets are loaded onto the polymer colloidal shell layer to obtain the photothermal working fluid.
8. The preparation method according to claim 7, characterized in that, In step S2, the crosslinking agent in the oil phase comes into contact with the functionalized polymer latex particles during emulsification and undergoes interfacial crosslinking.
9. The preparation method according to claim 7 or 8, characterized in that, The method for preparing the functionalized polymer latex particles includes: Using an amphiphilic functional polymer as a stabilizer, styrene monomer and 4-vinylbenzyl chloride were subjected to surfactant-free emulsion polymerization to obtain the functionalized polymer latex particles.
10. The application of a photothermal working fluid as described in any one of claims 1-6 in a solar photothermal conversion system, a direct absorption solar collector, a photovoltaic / photothermal system, or a solar thermal management system.